Molecular cloning, characterization and expression analysis of Toll-like receptor 5M gene in Japanese sea perch (Lateolabrax japonicas) after bacterial infection. (September 2016) - Wang, Chengyang; Zhao, Chao; Fu, Mingjun; Bao, Weiyang; Qiu, Lihua
Abstract: Toll-like receptor 5M belongs to Toll-like receptors (TLRs) family, which plays a crucial role in innate immunity due to its important role in the recognition of bacteria invasion and in the activation of immune related pathways downstream. In the present study, we firstly cloned the full-length cDNAs of TLR 5M ( LjTLR 5M ) from Japanese sea perch ( Lateolabrax japonicas ). The full-length cDNAs of LjTLR 5M include an open reading frame (ORF) of 2676 bp encoding a polypeptide of 891 amino acid residues. The deduced amino acid sequence analysis showed that LiTLR 5M contains LRRs (extracellular leucine rich repeats), transmembrane and TIR (Toll/interleukin-1 receptor) domain. Transcriptional expression analysis indicated that LiTLR 5M mRNAs were ubiquitously expressed in wide array of tissues and the peak level was observed in the head-kidney. The expression patterns of LjTLR 5M after Vibro harveyi and Streptococus agalactiae infection were detected by qRT-PCR, and the results showed that LjTLR 5M was significant up-regulated in spleen, liver and head-kidney. Additionally, the expression patterns of LjTLR 5M in infected spleen and head-kidney were further validated by in situ hybridization (ISH). In summary, these findings indicate that LjTLR 5M is significant induced after different bacterial infection and is involved in immune response. Furthermore, this study will provide foundational information for other TLRs research of L. japonicas against different bacterial pathogens invasion. Highlights: TLR 5M gene was identified and characterized in Japanese sea perch ( Lateolabrax japonicas ). The mRNAs of LiTLR 5M were ubiquitously expressed and the peak level was observed in the head-kidney. LjTLR 5M was up-regulated after Vibro harveyi and Streptococus agalactiae infection. LjTLR 5M plays an important role in L. japonicas immune response.